SPELEO-KINESIOTHERAPY - Neli Claudia Bîlha; Ştefan Bîlha; Andrei Bîlha (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The use of the therapeutic qualities of the microclimate from salt mines and the association with physical activity is realized from time to time, spontaneously or in an organized manner. The study comprises of an eclectic group (n=20) which took part in a rehabilitation program in the Cacica salt mine, Suceava County, for 3 weeks. A series of parameters that could have been influenced by the microclimate as well as by other therapeutically significant factors were analyzed. Speleokinesiotherapy is an example of general remodeling in rehabilitation, concept that we have introduced in 2010.